Research letter: Cardiovascular screening practices in US National Governing Bodies and National Paralympic Committees - Toresdahl, B. G.; Chang, C.; Confino, J.; Asif, I. M. (British Journal of Sports Medicine, 2017)
Cardiovascular screening in athletes has been a source of controversy within the sports medicine community. Annual screening inclusive of ECG is currently required by all major professional sports leagues in the USA and recommended by the IOC.1 In 2016, the American Medical Society for Sports Medicine (AMSSM) published a statement on cardiovascular screening, recognising knowledge gaps and advocating for medical providers caring for competitive athletes to consider important factors when determining an individualised cardiovascular screening strategy. These include the risk of sudden cardiac arrest (SCA) in the specific athlete population, the available resources and cardiology infrastructure for screening and secondary evaluations.2